Alcohol-induced liver disease: primary and secondary prevention - S. V. Plyusnin; K. V. Ivashkin; A. N. Bobrov; S. A. Belyakin; I. V. Plyusnina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To keep doctors and population in the picture of alcohol abuse issues and to acquaint with treatment approach at alcoholic disease, to prove necessity of primary and secondary prophylaxis.Key points. Alcoholism control efforts should be directed first of all on prevention of this disease. Primary prophylaxis is necessary for decrease or stop of alcohol consumption. It is required to educate population and to unveil myths about safe, and the more so useful dozes of alcohol. Secondary prophylaxis includes application of specific therapy with application of metabolic agents (hepatoprotectors).Conclusion. Alcohol is the main etiological factor of liver cirrhosis in Russia. Prompt change of situation with alcohol abuse is required for reduction of morbidity and mortality. Preventive actions should be directed on change of embedded stereotypes of doctors and population in relation to alcohol intake.